The Dynamic Observation of Plasma Concentration of Antimicrobial Agents During Balanced Ultrafiltration In Vitro. Issue 1 (19th July 2013) - Fang, Yinghui; Guan, Yulong; Wan, Caihong; Fu, Zhida; Jiang, Juanjuan; Wu, Chunfu; Zhao, Ju; Sun, Peng; Long, Cun
Abstract Routine perioperative intravenous antimicrobial agents are administered as surgical prophylaxis. However, whether balanced ultrafiltration during extracorporeal circulation has substantial effect on the concentration of antimicrobial agents remains unclear. The concentrations of antimicrobial agents in plasma and ultrafiltrate samples were measured in this pseudo‐extracorporeal circulation model. Extracorporeal circulation consisted of cardiotomy reservoir, membrane oxygenator, and pediatric arterial line filter. A hemoconcentrator was placed between the arterial purge line and oxygenator venous reservoir. Fresh donor human whole blood was added into the circuit and mixed with Ringer's solution to obtain a final hematocrit of 24–28%. Two kinds of antimicrobial agents, cefotiam (320 mg) and cefmetazole (160 mg), were bolus added into the circuit. After 30 min of extracorporeal circulation, zero‐balanced ultrafiltration was initiated and arterial line pressure was maintained at approximately 100 mm Hg with a Hoffman clamp. The rate of ultrafiltration (12 mL/min) was controlled by ultrafiltrate outlet pressure. An identical volume of Plasmalyte A was dripped into the circuit to maintain stable hematocrit during 45 min of experiment. Plasma and ultrafiltrate samples were drawn every 5 min, and concentrations of antimicrobial agents (including cefotiam and cefmetazole) were measured with high performance liquid chromatography. Both antimicrobial agents were detected in ultrafiltrate, demonstrating hemoconcentration may remove antimicrobial agents. The concentrations of plasma antimicrobial agents decreased linearly with the increase of ultrafiltrate volume. At end of balanced ultrafiltration, the concentration of plasma cefotiam was 104.96 ± 44.36 mg/L, which is about 44.38% ± 7.42% of the initial concentration (238.95 ± 101.12 mg/L) (P < 0.001); the concentration of plasma cefmetazole decreased linearly to 25.76 ± 14.78 mg/L, which is about 49.69% ± 10.49% of the initial concentration (51.49 ± 28.03 mg/L) (P < 0.001). The total amount of cefotiam in ultrafiltrate is 27.16% ± 12.17% of the total dose administered, whereas cefmetazole in ultrafiltrate is 7.74% ± 4.17%. Balanced ultrafiltration may remove antimicrobial agents from plasma and has a prominent influence on plasma concentration of antimicrobial agent. The strategy of surgical prophylaxis should consider this unique technique during extracorporeal circulation.